Clinical Features and Outcomes in Patients With Membranous Nephropathy and Crescent Formation. Issue 50 (December 2015) - Wang, Jia; Zhu, Ping; Cui, Zhao; Qu, Zhen; Zhang, Yi-miao; Wang, Fang; Wang, Xin; Wang, Jin-wei; Zhu, Sai-nan; Liu, Gang; Zhou, Fu-de; Zhao, Ming-hui
Abstract : Abstract: Cases of membranous nephropathy (MN) with crescent formation, in the absence of lupus, hepatitis B virus infection, anti-glomerular basement membrane (GBM) nephritis, or antineutrophil cytoplasmic antibody (ANCA), are on record. Clinical presentation and treatment outcomes in these patients are unclear. All patients with biopsy-proven MN diagnosed between years 2008 and 2014 and followed up were enrolled retrospectively. Patients with ANCA, anti-GBM antibodies, lupus, hepatitis B virus infection, or malignance were excluded. Clinical features and outcomes were compared between MN patients with and without crescent. Out of 401 consecutive patients with idiopathic MN, 28 (6.9%) showed crescent formation in 4.9% (2.2%–16.7%) of glomeruli. Mean age of these patients was 50.1 ± 11.1 years, and they presented with heavy proteinuria (6.5 ± 4.8 g/24 h) and hematuria; 21.4% of these patients had declined estimated glomerular filtration rate (<60 mL/min/1.73 m 2 ) on biopsy. Anti-phospholipase A2 receptor antibody was detectable in 79.7% of these patients. These clinical features were comparable to the MN patients without crescent ( P  > 0.05). Twelve (42.9%) patients received steroids plus immunosuppressive therapy similar to that in patients without crescent (41.3%). Fewer patients with crescents achieved remission (67.9% vs 86.7%, P  = 0.029). Crescent formation was a risk factor for no response to the treatments (odds ratio [OR] = 3.1, P  = 0.033). Higher percentage of crescents predicted more risk for no remission (OR = 1.2, P  = 0.038). Patients with crescents presented more frequencies of abnormal serum creatinine during follow-up (10.7% vs 1.3%, P  = 0.031). Crescent formation was also a risk factor for worse renal outcome (relative risk = 10.2, P  = 0.046). MN patients with crescents showed unfavorable therapeutic response and tended to have worse renal outcomes. More aggressive treatments and renal protection might be considered to improve the outcomes.